Thoracic outlet syndrome due to compression of subclavian artery at first rib - Shah, Akshay Hemant; Vyas, Sudhanshu R.; Dhond, Amit; Khedekar, Ravindra G.; Shetty, Sunil H. (International Journal of Research in Medical Sciences, 2017)
Thoracic Outlet Syndrome (TOS) refers to a constellation of signs and symptoms that arise from compression of the neurovascular bundle within the confined space of the thoracic outlet. Neurogenic (nTOS) from brachial plexus compression (95%), venous (vTOS) from subclavian vein compression (3%), & arterial (aTOS) from subclavian artery compression (1%). Most common clinical presentation of aTOS patients is distal upper extremity arterial emboli in otherwise healthy patient. Presenting a case report of arterial thoracic outlet syndrome.